Dynamic Behavior Analysis of Stochastic Nonautonomous Logistic Model with Limited Resources and Lévy Jump - Yonggang Ma; Junmei Liu (Discrete Dynamics in Nature and Society)
In this paper, we discuss the dynamic behavior of the nonautonomous stochastic logistic model under the influence of limited resources and Lévy jump. Firstly, by constructing the Lyapunov function and using the Itô formula, we prove the persistence and extinction of the solution of the model in the sense of p-moment. Secondly, with the help of the Itô-Lévy formula, we discuss that the zero solution and positive equilibrium solution of the model are almost asymptotically stable under certain conditions. Finally, we verified the correctness of these conclusions through numerical simulation and explained some specific biological significance.